Improving Natural Science Learning Outcomes on Energy and Its Changes Through Paired Practice Methods at MIS NU Ratan Daya - Fitriani, Ety (Jurnal Profesi Guru Indonesia, 2024)
The reality in Class III MIS NU Ratan Daya shows that, based on the daily test results, 4 out of 11 students achieved mastery, while 7 students did not. This indicates that the number of students who did not achieve mastery is greater than those who did. Based on the results of the pre-action test and initial observations, the researcher, who is also the class teacher, decided to implement a varied method that would engage students and make learning more exciting. In this case, the researcher used the paired practice method. This research employs the action research model, conducted in Class III MIS NU Ratan Daya. The researcher, who is also the teacher at this school, chose this school as the location for the study. The subjects of the study are the 11 students in Class III MIS NU Ratan Daya. The research was carried out during the beginning of the new school year 2022/2023, specifically from January to March 2023. Data collection techniques in this study include tests, observations, and documentation. The results of the pre-cycle test showed that the students' learning outcomes, in a classical sense, were 36.3%, categorized as "very low." In cycle I, the percentage increased to 63.6%, categorized as "high," and in cycle II, the percentage reached 100%, categorized as "very high." In cycle I, the class activity average was 2.85, which falls under the "good" criteria, and in cycle II, it increased to 3.21, still categorized as "good." The percentage of student activity in cycle I was 75%, categorized as "good," and in cycle II, the percentage increased to 85%, categorized as "very good." In addition to student activity, the study also evaluated learning outcomes. The results of the cycle II evaluation showed that the classical learning mastery reached 100%, with the final average score of students being 85.88. This was an improvement from the pre-cycle, where classical learning mastery was 36.3%, with an average score of 65.62, and from cycle I, where classical mastery was 63.6%, with an average score of 75. Based on these findings, it can be concluded that the paired practice method can be applied to the topic of energy and its changes and can significantly improve learning outcomes in Class III, Semester 2, MIS NU Ratan Daya for the 2022/2023 academic year.